PENGARUH DISKRIMINASI PAJAK, PEMAHAMAN PERPAJAKAN, DAN SANKSI PERPAJAKAN TERHADAP PERSEPSI PENGGELAPAN PAJAK PADA KPP PRATAMA SERPONG - Wulandari, Liana Novi; Sanulika, Aris (Jurnal Nusa Akuntansi, 2024)
This research aims to examine the influence of tax discrimination, understanding of taxation, and tax sanctions on perceptions of tax evasion. This research uses quantitative methods with an associative approach. The population is known to be 49,019 taxpayers, which is determined by the Slovin formula. The research sample was 100 respondents registered at KPP Pratama Serpong using SPSS version 25. The sampling technique used probability sampling with multiple linear regression analysis. Based on the research results, it shows that tax discrimination, understanding taxes and tax sanctions influence the perception of tax evasion both partially and simultaneously.